Previsão da demanda turística da cidade de Fortaleza: uma aplicação do modelo SARMA - Paiva, Edilva Praciano da Silva (2018)
The objective of this study is to forecast the tourist demand via Fortaleza, using the Box & Jenkins methodology. The time series refers to the monthly data of arrivals of tourists to Fortaleza between January 1997 and December 2016. As a result, we verify that the SARMA model presents the smallest means square root error than those of ARMA models.